Interaksi Lansia dengan Al-Quran: Studi Living Quran pada Pesantren Pemberdayaan Lansia Mukti Mulia Wedomartani, Ngemplak Sleman - Syarif Hidayat (STAI Terpadu Yogyakarta, 2020)
This paper aims to uncover the side of the interaction of the elderly with the Qur'an carried out and is in the activities of PesantrenPemberdayaan Lansia Mukti Mulia. This study is a study of the Living Qur'an. Living Qur'an Study is the study or scientific research on various social events related to the presence of the Qur'an or the existence of the Qur'an in a particular Muslim community. From there it will also be seen the social response (reality) of the Muslim community to make life and revive the Qur'an through a continuous interaction. Some forms of interaction between the elderly and the Qur’an at the Pesantren Pemberdayaan LansiaMukti Mulia are manifested in the activities of reading the Qur’an, tadarus, memorization of Surah, training in writing Arabic, studying the interpretation of the Qur’an and Mauidhatul Hasanah in each study.